2014
DOI: 10.1002/mrm.25139
|View full text |Cite
|
Sign up to set email alerts
|

Proton diffusion tensor spectroscopy of metabolites in human muscle in vivo

Abstract: Diffusivities, directional dependence of diffusion and fractional anisotropies of (1) H MRS-visible muscle metabolites were presented. It was shown that metabolites share diffusion directionality with water and have similar fractional anisotropies, hinting at similar diffusion barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…In that case, the sum spectra (including the motion‐corrupted scans) can be scaled such that the macromolecular peak is at a constant or expected level for each b ‐value. Such a correction scheme is similar to what had been suggested for investigations of metabolite diffusion in skeletal muscle, in which the lipid signals had been used as reference . The use of the macromolecular peak at 0.9 ppm for single shot outlier rejection has been used for animal studies but relies on much better SNR than available in our human studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In that case, the sum spectra (including the motion‐corrupted scans) can be scaled such that the macromolecular peak is at a constant or expected level for each b ‐value. Such a correction scheme is similar to what had been suggested for investigations of metabolite diffusion in skeletal muscle, in which the lipid signals had been used as reference . The use of the macromolecular peak at 0.9 ppm for single shot outlier rejection has been used for animal studies but relies on much better SNR than available in our human studies.…”
Section: Discussionmentioning
confidence: 99%
“…All experiments were conducted on 3T MR scanners (Verio, Trio, or Prisma; Siemens, Erlangen, Germany) using a single proton channel transmit–receive volume coil ( 1 H/ 31 P head coil; RAPID Biomedical, Rimpar, Germany) or multichannel head coils (20 or 32 channels). Based on the Siemens product STEAM sequence, a nWS‐DWS sequence (see Figure ) was implemented . Pairs of pulsed diffusion field gradients were inserted before and after the mixing time (TM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, effects of passive shortening and stretching of musculature and exercise effects on diffusion tensor characteristics have been examined successfully. Recent IVIM studies have reported on assessment of muscular perfusion and on diffusion tensor properties of metabolites visible in volume‐localized 1 H spectra .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, effects of passive shortening and stretching of musculature (21) and exercise effects (22,23) on diffusion tensor characteristics have been examined successfully. Recent IVIM studies have reported on assessment of muscular perfusion (24) and on diffusion tensor properties of metabolites visible in volume-localized 1 H spectra (25). Problems with noise (26), but also with 'data outliers' (27) and 'pulsation effects' from vasculature (28), were reported for DWI in several publications.…”
Section: Implications For Dwi Dti and Ivim Measurementsmentioning
confidence: 99%